The problem of the underachievement of the English working class at school: Special reference to the "community school" - Feidi-Maskell, Tina (The Greek Review of Social Research, 1980)
The argument around the problem of the working class underachievement at school has been moving away from the concept of cultural or linguistic deprivation of the working class student, which prevailed as a main explanation of the problem in the ’60’s. As a cause of the above issue there is, in the 70’s, a considerable emphasis upon the internal organization and the education content of the school which transmits the middle-class values of the society and represents the middle-class culture as «total culture». The «community school» in England within the radical approach has developed in an effort to search, mainly in socio-economically deprived areas, for alternative rather than traditional ways of affecting the school performance of the underachieving student. This outlook may involve radical change not only in the role of the school within its community, but in the selection and organization of knowledge at school as well.